Inhibitory Effects Induced by Vicia faba, Uncaria rhyncophylla, and Glycyrrhiza glabra Water Extracts on Oxidative Stress Biomarkers and Dopamine Turnover in HypoE22 Cells and Isolated Rat Striatum Challenged with 6-Hydroxydopamine - Orlando, Giustino (Antioxidants (Basel), 2019)
Background: Parkinson’s disease (PD) is the most common and progressive neurodegenerative and oxidative stress-related disorder, characterized by a dramatic loss of dopamine (DA) neurons in the nigrostriatal tissue. The first-line drug for PD treatment is represented by l-dopa, although clinical and preclinical studies pointed out the potential efficacy of medicinal plant- and food-derived antioxidants as brain protective agents. In this regard, the potential application of Vicia faba, Uncaria rhyncophylla, and Glycyrrhiza glabra extracts is of noteworthy interest, despite a lack of information in the scientific literature as regards their effect on striatal DA level. Methods: The protective effects of V. faba, U. rhyncophylla, and G. glabra water extracts were investigated on HypoE22 cells and isolated rat striatum specimens challenged with 6-hydroxydopamine (6-OH-DA). The extract effects against lactate dehydrogenase (LDH), nitrites, and 8-iso-prostaglandin(PG)F2α were evaluated using either single-extract treatments or a treatment with a pharmacological association. Additionally, the turnover of DA was measured. Results: The pharmacological association of the extracts was the most effective in contrasting the upregulated LDH and nitrite levels and in reducing striatal DA turnover. Conclusion: The present findings corroborate the rational for the traditional use of V. faba, G. glabra, and U. rhyncophylla extracts, supporting their pharmacological association in order to improve their protective effects.